Video-LLaVA-8B and LLaVA-NeXT Performance on HumanEval-V for Diagram-Based Code Generation - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 11 peer-reviewed papers addressing the following research question: How does Video-LLaVA-8B compare to LLaVA-NeXT on the HumanEval-V benchmark for diagram-based code generation accuracy. 13 claims were extracted from source literature; 1 was independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.2/10. This report is a machine-generated literature synthesis and does not constitute original rese
Machine-generated literature synthesis.